Analysis of downlink power control and cooperation scheme for two‐tier heterogeneous cellular network. (14th February 2017) - Swami, Pragya; Mishra, Mukesh Kumar; Trivedi, Aditya
Summary: The traditional cellular network cannot keep pace with the dramatic growth in data traffic due to exponentially increasing number of multimedia applications and mobile subscribers. Recently, femto base stations (FBSs) are deployed with the macro base station (MBS) tier for off‐loading the data traffic and to improve the indoor coverage of the heterogeneous cellular network. However, FBS deployment also increases the cross‐tier interference of the heterogeneous cellular network resulting in outage performance degradation of MBS tier. This work develops an analytical framework to limit the cross‐tier interference of MBS tier using power control scheme (PCS). The proposed PCS works on path loss inversion and location‐based power level rule for FBS. Moreover, a cooperation scheme and an association policy with MBS (CSAPM) are introduced to improve the outage performance of the FBS tier. Tools from the stochastic geometry are used for deriving the signal to interference and noise ratio outage probability, total outage probability, and area spectral efficiency (ASE) of MBS tier and FBS tier. Additionally, ASE maximization problem is formulated to evaluate the optimal density of FBSs. The effectiveness of the proposed PCS and CSAPM on outage performance and ASE are numerically demonstrated. It is noted from the results that the proposed CSAPM can compensate the loss in outage performance of FBS tier due to PCS. Finally, simulation results validate the analytical results. Abstract : In this work, a mathematical framework is developed to mitigate the cross‐tier interference of the macro base station (MBS) tier by using proposed power control scheme (PCS) for femto base station tier. This PCS operates on path loss inversion and location‐based power level rule. Moreover, a cooperation scheme and an association policy with MBS (cooperation scheme and an association policy with MBS) is suggested that makes up the loss in performance of femto base station tier due to applied PCS. The effectiveness of proposed PCS and cooperation scheme and an association policy with MBS on outage performance and area spectral efficiency are numerically demonstrated.